EVALUASI KINERJA PEMERINTAH DAERAH: PERAN BELANJA DAERAH DAN DANA PERIMBANGAN DENGAN OPINI AUDIT SEBAGAI MODERASI - Fadhila, Luthfiani; Utaminingtyas, Tri Hesti; Handarini, Dwi (LPPM Universitas Bina Bangsa, 2025)
This study was conducted to determine and analyze the impact of Regional Spending and Balanced Funds on Regional Financial Performance. The data used in this research is secondary data, sourced from budget realization reports. The unit of analysis is Provincial Government institutions that received audit opinions from 2015-2019. The sampling technique employed in this study is purposive sampling, resulting in 34 provinces with a total of 170 observations. The data analysis technique used in this research is Moderated Regression Analysis, with SPSS 27 as the analytical tool. The study's results indicate that Regional Spending and Balanced Funds have a significant impact, while Audit Opinions successfully moderate the effect of Regional Spending and Balanced Funds on Performance.